Contribution to the Study of Aplastic Anemia - Quesada Velásquez, Norberto (1965)
The term aplastic anemia has varied considerably in its true etymological sense , since its introduction in 1888 . Ehrlich (30 ) , at that time described a case of anemia, and thrombocytopenia Ieucopenia in the absence of marrow regeneration . Already B1umer ( 12) , in 1905 , the term aplastic anemia objects because many patients showed hypocellularity of the bone marrow, but this was normocellular . Subsequently Luzatto ( 78), two years later, described patients with pancytopenia with hypercellular bone marrow normocellular or under the name of seudoaplástica anemia. From this time have been used interchangeably , various denominations , with Rhoads and Baker ( 106 ) who try to unify the various manifestations of primary hematologic disorder of blood formation ; having studied in his review of 1938 , 100 cases of these patients , introducing the term refractory anemia, which divided into primary or idiopathic and secondary , but considering in the second tumor cases and aleucémicas leuccmias . Bomford and Rhoads, in 1941 , give greater certainty to the term refractory anemia, including cases C011 bone marrow fibrosis ( micloesclerosjs ) and others with immature bone marrow, without much evidence of anemia (chronic agranulocitis ) .